Analisis Daerah Rawan Bencana Tsunami Terhadap Pemanfaatan Lahan Perumahan dan Permukiman Kota Gunungsitoli Berbasis Geospasial - Junalisman Harefa; Zulkifli Zulkifli; Achmad Siddik Thoha (Jurnal Serambi Engineering, 2020)
Land-use pattern of Gunungsitoli municipality cannot be controlled yet, where land originally designated for the Local Protection Zone or the coastal green zone has been converted to function as built-up land for housing and settlement activities. Spatial Planning Law Number 26/2007, Regional Regulation No. 12/2012, and Presidential Regulation Number 51/2016 in Article (1) has regulated spatial layout and coastline. Research type used in this research is descriptive research with a qualitative-quantitative approach. This study aims to predict population growth in 2020-2039, land changes in 2010-2019 and distribution of tsunami prone areas analysis. The results of this study predict population growth in Gunungsitoli municipality for the next 20 years, 2020-2039, to 148.341 people. The biggest land use change / change analysis occurred in Gunungsitoli sub-district with a percentage of 25,38% of the total area of change in all Gunungsitoli sub-districts, and the smallest land use change’s percentage that occurred in Gunungsitoli West sub-district because this sub-district has a sloping and bumpy topography. The results of the tsunami disaster area analysis showed Gunungsitoli sub-district is the most extensive vulnerability impacted of 3.449 hectares. Subsequently followed by Gunungsitoli Idanoi sub-district, South Gunungsitoli sub-district and North Gunungsitoli sub-district.